Low Grade Fibromyxoid Sarcoma pada Pelvis yang Menyerupai Keganasan Ovarium: Laporan Kasus Salah Diagnosis Tanpa CT Scan Praoperatif - Puteri Moetia Charisma; Munizar Munizar; Hasanuddin Hasanuddin; Dewi Karlina Rusly; Fara Julyta Aliyah (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2026)
Low-grade fibromyxoid sarcoma (LGFMS) is a rare soft tissue tumor with deceptively benign histological features but significant potential for local recurrence and distant metastasis. Pelvic LGFMS is extremely uncommon and may mimic gynecological malignancies, leading to diagnostic challenges. This report describes a 39-year-old woman presenting with progressive abdominal enlargement, bloating, early satiety, and dyspnea. Physical and ultrasonographic examinations suggested a malignant ovarian tumor. The patient underwent exploratory laparotomy without preoperative CT scan evaluation. Intraoperatively, multiple solid masses involving the intestines, mesentery, omentum, peritoneum, and ovaries were identified, with the largest measuring 20 × 15 cm. Histopathological examination confirmed the diagnosis of LGFMS. The absence of preoperative cross-sectional imaging contributed to diagnostic difficulty in this case. CT scan and MRI are important for evaluating tumor origin, tissue characteristics, and involvement of surrounding structures. Definitive diagnosis requires histopathology supported by immunohistochemistry, particularly MUC4, and molecular confirmation when available. Comprehensive diagnostic evaluation is essential to avoid misdiagnosis, optimize management, and improve long-term outcomes in patients with pelvic LGFMS.